Effect of depth and vent fluid composition on the carbon sources at two neighboring deep-sea hydrothermal vent fields (Mid-Cayman Rise). (October 2015) - Bennett, Sarah A.; Dover, Cindy Van; Breier, John A.; Coleman, Max
Abstract: In this study, we have used stable isotopes of megafauna, microbial mats and particulate organic matter to examine the effect of depth and vent fluid composition on the carbon sources at two proximal, chemically distinct hydrothermal vent fields along the Mid-Cayman Rise. The basalt hosted Piccard vent field (4980 m) is twice as deep as the ultramafic hosted Von Damm vent field (2300 m) and has very different faunal assemblages. Of particular note is the presence of seep-associated fauna, Escarpia and Lamellibrachia tubeworms, at the Von Damm vent field. We identify a greater range of carbon sources and a suggestion of increased photosynthetic inputs to the Von Damm vent field compared to Piccard vent field. Rimicaris hybisae shrimp are the only abundant species shared between the two vent fields with δ 13 C values ranging between −22.7 and −10.1‰. Higher concentrations of hydrogen sulfide in the vent fluids at Piccard is proposed to be responsible for varying the relative contributions of the carbon fixation cycles used by their epibionts. Seep-associated fauna at Von Damm rely on elevated, thermogenic hydrocarbon content of the vent fluids for their carbon source (δ 13 C values ranging from −21.3 to 11.6‰). They also derive energy from hydrogen sulfide formed by the microbial reduction of sulfide (δ 34 S values ranging from −10.2 to −6.9‰). The tubeworms have very short roots (buried at most a centimeter into rubble), suggesting that microbial sulfate reduction must be occurring either in the shallow subsurface and/or in the anterior part of the tube. Overall, megafauna at Von Damm vent field appear to have a smaller food chain length (smaller δ 15 N range) but a greater breadth of trophic resources compared to the megafauna at the Piccard vent field. Highlights: A greater range of carbon sources have been identified at the shallower Von Damm vent field compared to the deeper Piccard vent field. Seep associated tubeworms rely on a thermogenic hydrocarbon source from the vent fluids. Microbial sulfate reduction at Von Damm either occurs in the shallow subsurface and/or in the anterior part of the tubeworm. Von Damm appears to have a smaller food chain length but a greater breadth of trophic resources compared to Piccard.